2002
DOI: 10.1074/jbc.m205895200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of T Cell Cytokine Production by Interferon Regulatory Factor-4

Abstract: Production of cytokines is one of the major mechanisms employed by CD4؉ T cells to coordinate immune responses. Although the molecular mechanisms controlling T cell cytokine production have been extensively studied, the factors that endow T cells with their ability to produce unique sets of cytokines have not been fully characterized. Interferon regulatory factor (IRF)-4 is a lymphoid-restricted member of the interferon regulatory factor family of transcriptional regulators, whose deficiency leads to a profoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 59 publications
3
77
0
Order By: Relevance
“…However, transfection experiments failed to confirm any role for this factor in arginase I regulation (data not shown). IRF-4 was appealing because it forms a complex with PU.1 that is understood in atomic detail (30), and plays an important role in regulating IL-4 responses (31)(32)(33)(34). However, macrophages from IRF-4 Ϫ/Ϫ mice had completely normal IL-4-mediated induction of arginase I (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…However, transfection experiments failed to confirm any role for this factor in arginase I regulation (data not shown). IRF-4 was appealing because it forms a complex with PU.1 that is understood in atomic detail (30), and plays an important role in regulating IL-4 responses (31)(32)(33)(34). However, macrophages from IRF-4 Ϫ/Ϫ mice had completely normal IL-4-mediated induction of arginase I (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Rengarajan et al (19) described that IRF-4 physically interacts with NFATc2 and enhances transcriptional activation of the IL-4 promoter. In human studies, Hu et al (27) reported that stable expression of IRF-4 in the Jurkat human T cell line led to production of Th2 cytokines and that IRF-4 binds the IL-4 promoter element triggering the transcription of IL-4. These studies used immortalized cells, which may represent effector/memory cell types, to evaluate the effect of IRF-4 on IL-4 production, and they are consistent with our observation that IRF-4 Ϫ/Ϫ CD4 ϩ T cells are defective in Th2 development and that IL-4 production by effector/memory IRF-4 Ϫ/Ϫ CD4 ϩ T cells is much lower than BALB/c CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…NFATc2 downregulates cyclin-dependent kinase 4 (CDK4) by directly binding and repressing its transcription through the recruitment of histone deacetylase (Baksh et al, 2002). NFATs act synergistically with other proteins (Lim et al 2008) such as AP-1 (Wisniewska et al, 2007), and IRF (Hu et al, 2002). Although we have reported that IRF molecules are involved in TR2 regulation (Sul et al, 2008), the interaction of NFATs with other proteins, and the precise mechanism of regulation of TR2 gene expression, require further investigated.…”
Section: Discussionmentioning
confidence: 93%